Gotong Royong dan Tanggung Jawab Sosial sebagai Civic Engagement: Tinjauan Sosiologi Kewarganegaraan dalam Perspektif Robert Putnam - Mike Meida Diningrum; Budi Mulyono (Integralistik, 2026)
The phenomenon of weakening social solidarity and increasing individualism in modern society reminds us of the importance of revitalizing the values ​​of mutual cooperation and social responsibility as part of citizenship practices. This study aims to analyze these two values ​​from the perspective of Robert Putnam's civic engagement as a form of social capital that strengthens public participation, trust, and community solidarity. The study uses a qualitative descriptive-analytical method with a library research approach through content analysis of various scientific literature sourced from Google Scholar, Mendeley, SINTA, and Scimago Journal and Country Rank. The results of the study indicate that mutual cooperation and social responsibility have a strategic role in strengthening citizen engagement amidst the challenges of globalization and digitalization that tend to encourage individualistic lifestyles. This study contributes to strengthening the concept of civic engagement based on local cultural values ​​through the integration of Robert Putnam's thoughts with the values ​​of mutual cooperation and social responsibility as a foundation for strengthening civic participation in the modern era.